Spontaneous Gastric Necrosis: A Rare Presentation of Invasive Mucormycosis in an Immunocompetent Adult. (25th July 2020) - Hameed, Tariq; Jain, Sudhir Kumar; Ansari, Faiz Manzar; Nizam, Adiba; Dua, Amrita
Abstract : Spontaneous gastric perforations are usually seen in patients with untreated peptic ulcer disease. Mucormycosis, an uncommon, opportunistic, life-threatening fungal infection, rarely causes gastric perforation in immunocompetent adults. Here, we present a case of young female who was admitted to hospital for acute pain abdomen and distension with 5 days history of fever. She was operated and was found to have multiple perforations in the stomach with transmural necrosis. Despite adequate surgical excision and intravenous amphotericin B, patient succumbed to sequelae of infection.